2017
DOI: 10.1002/term.2238
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-activated serum might have a therapeutic effect on damaged articular cartilage

Abstract: Platelet-activated serum (PAS) was collected from rabbits. This contains high concentrations of growth factors, including vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF)-BB, and transforming growth factor-beta (TGF-β). PAS was injected into the knee joints of Japanese White rabbits subjected to anterior cruciate ligament transection (ACL-T) to investigate its therapeutic effects on articular cartilage. The effect of Avastin (an anti-VEGF monoclonal antibody) on VEGF expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…PRP, a concentrated platelet obtained by centrifugation of peripheral blood, consists mainly of platelet-associated leukocyte aggregation, high-density fibrous network structures, platelet-derived growth factors, transforming growth factor-beta, insulin-like growth factor, epidermal growth factor and vascular endothelial growth factor. [ 34 , 35 ] PRP releases a large number of growth factors to promote cell proliferation and regulate cell behavior and antiinflammatory factors to reduce local inflammation. [ 36 ] In recent years, its role in cartilage injury repair has drew increasing attention.…”
Section: Discussionmentioning
confidence: 99%
“…PRP, a concentrated platelet obtained by centrifugation of peripheral blood, consists mainly of platelet-associated leukocyte aggregation, high-density fibrous network structures, platelet-derived growth factors, transforming growth factor-beta, insulin-like growth factor, epidermal growth factor and vascular endothelial growth factor. [ 34 , 35 ] PRP releases a large number of growth factors to promote cell proliferation and regulate cell behavior and antiinflammatory factors to reduce local inflammation. [ 36 ] In recent years, its role in cartilage injury repair has drew increasing attention.…”
Section: Discussionmentioning
confidence: 99%
“…PRP mainly includes platelet-related leukocyte aggregates, high-density fibrous network structure, platelet-derived growth factor, transforming growth factor-β, insulin-like growth factor, epidermal growth factor, and vascular endothelial growth factor. 4142 PRP can release a large number of anti-inflammatory factors to reduce local inflammation and can release a variety of growth factors to promote cell proliferation and regulate cell behavior. 43 In vitro studies have shown that chondrocytes and PRP exhibit a significant dose- and time-dependent increase in cell number and metabolic cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation, platelet alpha-granules secrete high concentrations of GFs, such as transforming growth factor β (TGF-β) and platelet-derived growth factor (PDGF). 55 TGF-β serves as one of the most important GFs involved in cartilage regeneration by increasing chondrocyte phenotype expression and matrix deposition, 10,47 promoting MSC chondrogenic differentiation, 37 and counteracting the suppressive effects of inflammatory mediators on cartilage-specific macromolecule synthesis. 40 PDGF favors the maintenance of hyaline-like chondrogenic phenotype, increases chondrocyte proliferation and the synthesis of proteoglycans, and is a potent chemotactic factor for all cells of mesenchymal origin.…”
Section: Discussionmentioning
confidence: 99%